Approaches to psycho-pedagogical examination of game playgrounds - Kotliar I.A.; Sokolova M.V. (Современная зарубежная психология, 2016)
The article is devoted to the problem of the game environment - playgrounds. The article discusses the history of children's playgrounds, analyses the different methodological approaches to their expertise: an ecological approach, socio-cognitive approach, subjective or personal approach, activity approach. Taking into account the latest contemporary foreign researches, the article discusses the facts concerning the link between the types of playgrounds, their equipment and the nature of child behavior. The article provides basic criteria for expertize of game environment: game value of plating objects or game environment in general, landscape features of playgrounds, the elements that trigger risky behavior, etc. The conclusion states that playgrounds must be assessed in terms of their compliance to the needs of children and the age related challenges of their development.